Textbook praxeological-didactical analysis: Lessons learned from the Indonesian mathematics textbook - Yunianta, Tri Nova Hasti; Suryadi, Didi; Dasari, Dadan; Herman, Tatang (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2023)
The objective of textbook study is to create high-quality textbooks. Analysis was done using a praxeological-didactical analysis (PDA) method. PDA offers space to analyze curriculum materials, such as math textbooks, which are the outcome of human action in the anthropology of a specific nation's society. There are 10 types of tasks given in the mathematics textbook on measurement of spatial figures and seven techniques are identified as possible ways to complete the tasks. The justification of praxis is that there are three emerging technologies and two theories that are used as the final direction of the given task type. There is a sequence of task composition at the start with loads at level 2 and level 3 that can affect student readiness. Psychologically, it is regarded as difficult at first, which can lead to students becoming disinterested as well as bored, thus experiencing difficulties, creating ontogenetic obstacles. The other predicted learning obstacles identified in this textbook are epistemological and didactic obstacles. All the findings from this analysis can be applied to continuously raise the standard of the currently available mathematics textbooks.